Constructed Identities and Dueling Ideologies: Reading Ancient Israelite Foreign Oracles as Ideological Critique - Timmer, Daniel C. (Biblical interpretation, 2024)
This article aims to advance understanding of foreign nation oracles in the hb/ot by analyzing how many such oracles focus, more precisely, on subgroups within the polities named and direct their critique against that group’s articulation and enactment of imperialistic or nationalistic ideologies. The article first draws upon sociology and critical discourse analysis to sketch a theoretical perspective in which to analyze such oracles, then heuristically explores nation oracles in several prophetic books to illuminate the significance of their double focus on subgroups associated with ideologies which, as discourses of power, definitively validate and vindicate their proponents over against the Other. The article concludes with reflections on the value of ideologically-sensitive interpretation of prophetic oracles concerning foreign groups in light of this phenomenon’s overlap with sociology, imperialism, ideological critique, and justice.